Armed Conflict in Colombia: A Review from the Impacts and Contributions of Education - Aristizábal, Luz Adriana; Ávila, Adriana Inés (Journal of Education Culture and Society, 2025)
Thesis. The armed conflict in Colombia has had a profound impact on education, affecting teachers, students, families, and communities. This review aims to examine the effects of the conflict on education and explore the contributions of education in promoting peace and social reconstruction. Concept. Key concepts addressed include human rights, peace-building through education, and the role of education in conflict transformation. Education, shaped by violence, has become both a tool for addressing human rights violations and a means of fostering peace and justice in conflict-affected regions. This qualitative study employs a documentary review approach, analysing 123 articles and theses published between 1996 and 2020. From these, 40 were selected based on their relevance to the research topic, providing a comprehensive understanding of the intersection of armed conflict and education in Colombia. Results and Conclusion. The review reveals significant human rights violations against teachers in Colombia. Despite these challenges, various efforts have been made to promote peace through education, including community initiatives and policies aimed at transforming conflict into opportunities for justice and peace. Education is shown to not only respond to violence but also actively contribute to societal transformation. Originality. This study offers an original contribution by examining the role of education in addressing the impacts of the armed conflict and promoting peace in Colombia, focusing on educators’ experiences and their contributions to societal reconstruction.